Patrones de distribución ficoflorística en el sistema lagunar de Nichupté, Quintana Roo, México - Collado-Vides, Ligia; Gonzalez-Gonzalez, Jorge; Ezcurra, Exequiel (Instituto de Ecología, A.C., 1995)
A study on the algal distribution in the Nichupte Lagoon System (NLS) was done. The NLS is a coastal lagoon in the state of Quintana Roo, in the coast of the Caribbean Sea. It has mostly marine water. The sandy sediments are covered with patches of seagrasses and the borders present mangrove growths. A total of 77 species was found, distributed in the following divisions: 33 in Chlorophyta, 37 in Rhodophyta, 3 in Phaeophyta and 4 in Cyanophyta. A significant floristic difference was found between the samples collected in the sandy places and those on the roots of mangroves. The main differences in floristic composition were associated with substratum, depth and salinity.